Skin microneedling alone versus skin microneedling plus Platelet rich plasma PRP in the treatment of atrophic post acne scars (A split face comparative study) - Saleh, Lina Hasan; Alkhayer, Abdullah Ezzeldin (Journal of medical and pharmaceutical sciences, 2022)
Objective: The aim of this study is to compare the efficacy of microneedling(MN) followed by platelet rich plasma(PRP) with microneedling alone in the treatment of atrophic acne scars.Patients and Methods: Experimental study without controlled study conducted for the period one year (May 2020- May 2021) at Tishreen University Hospital in Lattakia- Syria. The study included 35 patients with atrophic acne scars who received MN with PRP on the left side of the face (group I), and MN alone on the right side (group II).Results: Mean age was 29.7±7.8 years, the most frequent age group was 20- 30 year (62.9%), and female represented 62.9% of the patients. Acne scars ranged in severity from moderate (38.6%) to severe (55.7%), and boxcar was the most frequent type (41.4%). A statistically significantly reduction was occurred at the end of treatment in group I (6.37±3.5 vs 12.80±3.9) and group II (8.57±4.2 vs 11.88±4.5) according to Goodman and Barron, but the reduction was higher in groupI. The best therapeutic results (excellent and good) were obtained in groupI especially in boxcar type. Regarding of side effects, pain, edema, and erythema were occurred in all cases in the two group, and the mean duration of edema and erythema was significantly shorter in group I.Conclusion: Combination of MN and PRP was found to be safe and efficacious in the treatment of atrophic acne scars.
Keywords: acne scars; microneedling; platelet rich plasma